Proximate and Mineral Compositions of Rice Field Eel Monopterus Albus - Arizal, Muslimatun; Syakirah Hanim Mohd-Khairi, Nor; Chew Ha, Hou; Ing Nguang, Siew; Ikhwanuddin, Mhd; Chee Poh, Seng; Fay Komilus, Connie (International Journal of Engineering and Technology, 2018)
Rice field eel (Monopterus albus) is an air breather freshwater fish that can be found extensively in paddy field area in Malaysia. It has high economic value all over Asia and used as folk remedies for various diseases. Mineral compositions play a vital role in various metabolisms though it’s required in a minute amount in the human body. Proximate compositions and selected minerals compositions were determined in Monopterus albus. The study found that Monopterus albus was high in protein content (50.07%-74.31%) and low in lipid (2.26%-2.66%), which suggests this fish species suitable to be consumed by various human conditions. The amplest macroelement was Calcium with a concentration of 29127.00 mg/Kg - 50468.50 mg/Kg, followed by Phosphorus and Magnesium, 21290.00 mg/Kg - 32975.50 mg/Kg and 1264.50 mg/Kg - 1638.50 mg/Kg respectively. Zinc was the dominant microelement found in Monopterus albus with a concentration ofÂ 44.17Â±1.20 mg/Kg followed by Iron, Manganese, Copper, and Chromium with concentration range of 32.60 mg/Kg - 38.6 mg/Kg, 3.40 mg/Kg â€“ 22.65 mg/Kg, 0.97 mg/Kg - 1.07 mg/Kg and 0.59 mg/Kg - 0.78 mg/Kg respectively.Â The results of this study will be further used to promote fish-based medication and remedies benefit to human.Â Â